Enhanced force production in old age is not a far stretch: an investigation of residual force enhancement and muscle architecture. Issue 1 (7th June 2013) - Power, Geoffrey A.; Makrakos, Demetri P.; Rice, Charles L.; Vandervoort, Anthony A.
Abstract: In older adults, isometric force production is enhanced following a voluntary lengthening contraction when compared with isometric force produced at the same muscle length without a prior lengthening contraction. This phenomenon is termed residual force enhancement (RFE), and appears to be related to the age‐related maintenance of eccentric (ECC) strength. However, it is unknown whether age‐related changes in muscle architecture contribute to greater RFE at short and long muscle lengths in old age. Neuromuscular properties of the knee extensors were assessed on a HUMAC NORM dynamometer. Torque was examined in young (26 ± 3 year, n  = 11) and old men (77 ± 6 year, n  = 11) during brief maximal voluntary isometric contractions (MVC) at 80° and 120° (180° representing full knee extension) and then compared with torque during a steady‐state phase at the same joint angle following a maximal voluntary lengthening contraction at 30°/sec over a 60° joint excursion; either from 140 to 80° (long), or from 180 to 120° (short). Ultrasound images were obtained from the vastus lateralis during the isometric phase for each condition. When comparing the ECC torque with the MVC isometric torque, old men had 17% greater ECC:MVC ratios than young men, confirming an age‐related maintenance of ECC strength. The extent of RFE was greater at long versus short but independent of age. At rest, old had shorter (~18%) and less pennated (~22%) fascicles. However, changes in fascicle length and pennation during contraction did not contribute to RFE in either group. Thus, age‐related changes in muscle architecture may not contribute to RFE. Abstract : e00004 Abstract : Ultrasound images from a representative older adult at LONG muscle length showing fascicle length (FL) and angle of pennation (β) measurement at rest, during the isometric reference MVC, and during the isometric steady‐state following lengthening.